Paradiplomasi Desa dalam Arus Globalisasi: Studi Kegiatan Sunday Morning sebagai Diplomasi Lokal Berbasis Komunitas di Desa Pengarasan, Kecamatan Bantarkawung, Kabupaten Brebes - Fany Anggun Abadi; Azmy Habib Mukhyidin; Ridha Nahdhiyah Alma Amaliyah; Aqib Ardiansyah (Universitas Negeri Gorontalo, 2026)
Globalization has transformed the actors in international relations, which are no longer dominated by states as the sole primary actors. Local actors such as village governments and community groups now play a strategic role in building global interactions through social, cultural, and lifestyle practices. This article aims to analyze the Sunday Morning activity in Pengarasan Village as a form of local diplomacy within the perspective of globalization. The study employs a qualitative method using a case study approach through participatory observation and community interviews. The findings show that the Sunday Morning activity is not merely a community sports activity but also functions as an instrument of paradiplomacy, strengthening local identity while adopting global healthy lifestyle trends. These findings affirm that villages can act as non-state actors in international relations through community-based social practices.